The Spectacular Crowd: Representing the Masses in DV Documentary - Shen, Shuang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In their introduction to a collaborative study of crowds organized by the Stanford Humanities Lab in 2000, Jeffrey T. Schnapp and Matthew Tiews observe that while the first half of the twentieth century witnessed a rise of collective social action and various forms of mass assembly, the second half was a period of the decline of collective political formations and the replacement by virtual and media-based assemblies for physical crowds (Schnapp and Tiews 2006, xi). The postindustrial political economy in the West is “characterized by the coexistence of media aggregation and bodily disaggregation,” Schnapp and Tiews claim (xi).
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé